Influence of Solution Heat Treatment on Microstructure and Tensile Properties of Gd-Treated Al-15% Mg2Si In-Situ Composites - Hamidreza Ghandvar; Tuty Asma Abu Bakar; Mohd Hasbullah Idris (Journal of Applied Science and Engineering, 2021)
Microstructural alteration and tensile properties of Al-15% Mg2Si composite specimens was examined after addition of gadolinium (Gd) and conducting solution heat treatment. Various percentages of gadolinium (0.5, 1.0, 2.0 and 5.0 wt. % Gd) were added to the composite Al-15% Mg2Si composite. The specimens then solutionized at 500 °C for 4h followed by quenching. The results showed that regular morphology and small size of primary Mg2Si particles is achieved after addition of 1.0 wt.% Gd compared to untreated composite. Due to solutionizing effect, Mg2Si dissolution occurred which led to alter the morphology of primary Mg2Si particles to round shape. Tensile testing results revealed that enhancement in UTS and El% values owns to influence of both Gd addition and solution heat treatment on the Al-15% Mg2Si composite. The fracture surface of untreated composite depicted a cellular fracture, while the fracture surface of Gd treated and heat treated composite showed a ductile surface containing fine dimples, in which alteration of fracture mode is due to the role of Gd and heat treatment on microstructural modification, which results in reduction of potential sites for stress concentration and crack initiation areas.